Knockdown of USP39 by lentivirus-mediated RNA interference suppresses the growth of oral squamous cell carcinoma - Li, Ke-Yi; Zhang, Jie; Jiang, Li-Cheng; Zhang, Bin; Xia, Chun-Peng; Xu, Kai; Chen, Hai-Ying; Yang, Qiao-Zhi; Liu, Shu-Wei; Zhu, Hong (Cancer biomarkers : section A of Disease markers, 2016)
Oral squamous cell carcinoma (OSCC) is a frequently diagnosed life-threatening oral cancer worldwide and has become one of the leading causes of cancer-related mortality. However, the pathogenesis of this disease is very limited. In this study, we aimed to investigate the functional relationship between OSCC and a potential tumor related gene ubiquitin-specific proteases 39 (USP39). The lentivirus-based RNA interference was utilized to knock down USP39 expression in human OSCC CAL27 cells. The effect of USP39 on cell proliferation was detected by MTT and colony formation assays. The results uncovered that the proliferation rate was significantly decreased in specific USP39-targeting lentivirus infected cells compared to control lentivirus infected cells. The colony formation capacity was also attenuated in CAL27 cells after USP39 knockdown. Moreover, knockdown of USP39 arrested CAL27 cells in S and G1/M phases of the cell cycle. Furthermore, USP39 silencing induced apoptosis of CAL27 cells via activations of Caspase 3 and PARP. In conclusion, the inhibition of USP39 in CAL27 cells suppressed cell growth probably via induction cell cycle arrest and apoptosis. USP39 might act as an oncogenic factor in OSCC and could be a potential molecular target for OSCC gene therapy.